2015
DOI: 10.1007/s00784-015-1497-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of immune genes in long-term cultured dental stem cells

Abstract: A complete biological characterization covering all major aspects including immune properties should be made as prerequisite criteria prior to the use of long-term cultured stem cells in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
8
0
4
Order By: Relevance
“…A previous study showed that BMMSCs maintain stable properties in vitro during the first 6‐8 passages of expansion culture and enter a phase of senescence within 7‐12 passages . As for dental MSCs, Pukana Jayaraman considered P9 cells were long‐term cultured dental stem cells . Studies about DPSCs also showed that the differentiation potential of DPSCs is restricted at the 9th passage and senescence of DPSCs may occur after the 10th passage .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that BMMSCs maintain stable properties in vitro during the first 6‐8 passages of expansion culture and enter a phase of senescence within 7‐12 passages . As for dental MSCs, Pukana Jayaraman considered P9 cells were long‐term cultured dental stem cells . Studies about DPSCs also showed that the differentiation potential of DPSCs is restricted at the 9th passage and senescence of DPSCs may occur after the 10th passage .…”
Section: Discussionmentioning
confidence: 99%
“…However, PDLSC proliferation remains slow under the current culture conditions. More importantly, these cells inevitably undergo replicative senescence, resulting in potential cellular phenotypic changes and/or loss of cell stemness (Kim et al 2009;Jayaraman et al 2016). Indeed, there is evidence that the in vitro lifespan of PDL-derived cells is shorter than that of other cell types in connective tissues (Sawa et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, maintaining the stemness of PDLSCs, particularly with regard to their migration, proliferation and differentiation, has become a vital issue that must be carefully addressed before these cells enter the clinical testing stage . Clearly, the current in vitro system cannot replicate the desired in vivo environment, which consists in various factors, such as oxygen tension, biochemical molecules and mechanical forces (Ashton et al 2011), generally leading to low-quality cellular products with impaired proliferation, early senescence and/or the loss of regenerative potential (Sawa et al 2000;Kim et al 2009;Jayaraman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The application of hDPSCs as a model of study was useful due to its multipotentiality in differentiating into several cell types (Pierdomenico et al, 2005) and to present a low immunogenicity (Gronthos, Mankani, Brahim, Robey, & Shi, 2000). In addition, hDPSCs are mesenchymal stem cells (MSCs) that are easy to isolate and culture, and it does not face ethical barriers since its source is a tissue that would normally be discarded after, for example, dental extractions (Arany et al, 2014;de Sá Silva et al, 2012;Ding, Niu, & Liu, 2015;Gronthos et al, 2000;Jayaraman et al, 2016). associated with growth factors (Diniz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%